Analisis Faktor Penyebab Kejadian Hipertensi di Wilayah Puskesmas Beji Depok: Analysis of factors causing the incidence of hypertension in the Beji Depok Community Health Center area - Asri, Intan Puspita; Putri, Anna Maryanah; Afifah, Faidah; Khairunnisa, Aisyah; Salamah, Nurul Pitriani; Putri Nabila, Shofia; Kusumastuti, Istiana (Journal of Public Health Education, 2023)
Background: Hypertension is one of the non-communicable diseases often referred to as "the silent killer" because it frequently occurs without symptoms, leaving the affected individuals unaware of their hypertension. Subsequently, they may discover complications or complications arising from hypertension. Objective: To analyze the factors causing hypertension in the Beji Primary Health Care (Puskesmas) area, Depok. Method: This research utilizes a descriptive-analytic research method aimed at identifying health problems, determining the causes of health problems, and providing alternative solutions to health problems or the suboptimal implementation of Health Service Programs in a health service institution. It also considers the health profile of Depok City and several previous journal studies. Results: The study indicates that genetic factors (heritage), behavioral factors (physical activity, food and beverage consumption, and the use of antihypertensive drugs) influence the occurrence of hypertension. Conclusion: Factors related to the occurrence of hypertension in the Beji Depok Health Center from 60 respondents show that community health behavior in daily life is still inadequate in 42 individuals (70%), knowledge about hypertension is insufficient in 36 individuals (60%), and irregular consumption of antihypertensive drugs is noted in 42 individuals (70%).